Quantitative relationships between investments in farms and environmental effects in some European countries - Galluzzo, Nicola (Journal of Agricultural Sciences (Belgrade), 2017)
Since the early 1970s, in many European countries member of the European Union there has been a significant improvement in their own agricultural economic growth due to the Common Agricultural Policy. The in arising levels of investment in land and in machinery has been one of the pivotal pillars in improvement levels of food self-sufficiency. However, a growth in investments has increased pollutant emission in terms of carbon dioxide, nitrogen sub products and a deterioration of environment. The purpose of this paper was to investigate the impact of investments on agricultural and arable land in improving agricultural production towards environmental quality. The quantitative methods has used a neural relation analysis through the Kohonen’s maps or Self-Organizing Maps (SOM). Findings of Kohonen’s maps have pointed out a good ability to classify the time series data and its spatial evolution; furthermore, SOMs have been useful in describing the impact of investment on production specialization, levels of pollution and food self-sufficiency in the European countries. To sum up, an improvement of food self-sufficient level has been tightly linked to an increase of pollution in terms of carbon dioxide emissions.